Understanding Parents' Self-Awareness of Their Parenting Style(s) and Its Influences on Their Parenting Choices - A Grounded Theory Study. (July 2023) - Rutigliano, Bridget E.; Randolph, Amber L.; Park, Candace N.
Parenting is a process made up of approaches, styles, and daily choices. Parents are often unaware of how much their parenting style can impact the choices they make each day related to parenting their children. This grounded theory study explored how parents' self-awareness of their parenting styles influences parenting choices in a sample of parents with children ages birth-11. Seven main themes emerged from this study: (a) the role of comparison and impact of social media, (b) parents do the best they can based on what they have learned and experienced, (c) promoting mental health and wellbeing in what is typically an autopilot experience, (d) parenting is hard, and it can be lonely, (e) navigating the impact of childhood experiences, (f) pressure to be perfect; not enough time to get it all right, and (g) intentionality through self-awareness and reflection. Upon further reflection on the themes, the following theory emerged: Parenting is hard, and it can be a lonely journey. Parents do the best they can based on their experiences and comparing to others. However, when invited to reflect on their parenting choices, parents are more intentional through self-awareness and promoting their mental health and wellbeing. This study's findings offer implications for counselor education as they underscore the need for CACREP (2016) to implement a formal standard to guide counselor training programs to offer instruction relating to parenting styles.